Presentation of an unusual sized peripheral cement-ossifying fibroma: case report - Barbieri , Melina (2025)
Peripheral cemento-ossifying fibroma (PCOF) is a benign reactive gingival lesion, commonly associated with chronic local irritants and with a predilection for young women. Although it typically appears as a small, asymptomatic, and slow-growing mass, atypical presentations with larger size and aggressive behavior have been reported. Definitive diagnosis relies on histopathological analysis, and the treatment of choice is complete surgical excision along with the removal of local etiological factors to minimize recurrence risk. This article reports the case of a 34-year-old female patient with a large (10 × 5 cm), rapidly growing mandibular PCOF that caused facial asymmetry, tongue displacement, functional impairment, and bone involvement. The lesion was successfully treated through surgery under general anesthesia, with favorable postoperative recovery. This case highlights an uncommon presentation of PCOF and underscores the importance of early diagnosis and wide surgical management in atypical clinical forms.